Interferonβ-1b Induces the Expression of RGS1 a Negative Regulator of G-Protein Signaling - Tiffany Tran; Pedro Paz; Sharlene Velichko; Jill Cifrese; Praveen Belur; Ken D. Yamaguchi; Karin Ku; Parham Mirshahpanah; Anthony T. Reder; Ed Croze (International Journal of Cell Biology)
We present evidence of a link between interferonβ-1b (IFN-β) and G-protein signaling by demonstrating that IFN-β can induce the expression of the negative regulator of G-protein signaling 1 (RGS1). RGS1 reduces G-protein activation and immune cell migration by interacting with heterotrimeric G-proteins and enhancing their intrinsic GTPase activity. In this study, IFN-β treatment resulted in the induction of RGS1 in peripheral blood mononuclear cells (PBMCs), monocytes, T cells, and B cells. Induction of RGS1 by IFN-β was concentration dependent and observed at both the RNA and protein level. Other members of the RGS family were not induced by IFN-β, and induction of RGS1 required the activation of the IFN receptor. In addition, RGS1 induction was observed in PBMCs obtained from IFN-β-treated multiple sclerosis patients suggesting a possible, as yet unexplored, involvement of G-protein regulation in disease treatment. The upregulation of RGS1 by IFN-β has not been previously reported.